Case Report: X-Linked SASH3 Deficiency Presenting as a Common Variable Immunodeficiency - Labrador-Horrillo, Moisés; Franco-Jarava, Clara; Garcia-Prat, Marina; Parra-Martínez, Alba; Antolín, María; Salgado-Perandrés, Sandra; Aguiló-Cucurull, Aina; Martinez-Gallo, Mónica; Colobran, Roger (Frontiers in Immunology, 2022)
SASH3 is a lymphoid-specific adaptor protein. In a recent study, SASH3 deficiency was described as a novel X-linked combined immunodeficiency with immune dysregulation, associated with impaired TCR signaling and thymocyte survival in humans. The small number of patients reported to date showed recurrent sinopulmonary, cutaneous and mucosal infections, and autoimmune cytopenia. Here we describe an adult patient previously diagnosed with common variable immunodeficiency (CVID) due to low IgG and IgM levels and recurrent upper tract infections. Two separate, severe viral infections drew our attention and pointed to an underlying T cell defect: severe varicella zoster virus (VZV) infection at the age of 4 years and bilateral pneumonia due type A influenza infection at the age of 38. Genetic testing using an NGS-based custom-targeted gene panel revealed a novel hemizygous loss-of-function variant in the SASH3 gene (c.505C>T/p.Gln169*). The patient’s immunological phenotype included marked B cell lymphopenia with reduced pre-switch and switch memory B cells, decreased CD4+ and CD8+ naïve T cells, elevated CD4+ and CD8+ TEMRA cells, and abnormal T cell activation and proliferation. The patient showed a suboptimal response to Streptococcus pneumoniae (polysaccharide) vaccine, and a normal response to Haemophilus influenzae type B (conjugate) vaccine and SARS-CoV-2 (RNA) vaccine. In summary, our patient has a combined immunodeficiency, although he presented with a phenotype resembling CVID. Two severe episodes of viral infection alerted us to a possible T-cell defect, and genetic testing led to SASH3 deficiency. Our patient displays a milder phenotype than has been reported previously in these patients, thus expanding the clinical spectrum of this recently identified inborn error of immunity.